Caregiver and child perspectives of wellbeing in school-age children with childhood apraxia of speech. - Turner Swartz, Michelle; Hitchcock, Elaine R.; Leece, Megan C.; Herbst, Benedette M.; Preston, Jonathan L. (International Journal of Speech-Language Pathology, 2025)
Purpose: Childhood apraxia of speech (CAS) is a communication deficit that impacts a child's overall quality of life, including their academic and social interactions, yet few studies have investigated the impact from the child's perspective. Using The World Health Organization's International Classification of Functioning, Disability, and Health (ICF) framework, we examined the children's and caregivers' perspectives on the impact of CAS on their overall wellbeing. Method: Survey data were collected from 32 child-caregiver dyads for children ages 9–17 years with CAS. Items elicited responses along a 5-point scale to examine the perceived impact of children's speech impairments using the framework, including impact on communication, interpersonal interactions/relationships, and major life events. Result: Results from non-parametric statistical analyses revealed: (a) caregivers reported a significantly greater impact than children across individual ICF domains; (b) child responses were not significantly correlated with their caregiver's responses or with the child's age, gender, or severity indicators; and (c) both caregivers and children indicated the domain of communication was impacted more than other domains. Conclusion: Results suggest a potential disconnect in the perceived impact of CAS between the caregiver and child. Recommendations include facilitating a dialogue between the child-caregiver dyad and considering treatment goals that address wellbeing.